Biophysical Support for Functionally Distinct Cell Types in the Frontal Eye Field - Cohen, Jeremiah Y. (American Physiological Society, 2009)
Numerous studies have described different functional cell types in the frontal eye field (FEF), but the reliability of the distinction between these types has been uncertain. Studies in other brain areas have described specific differences in the width of action potentials recorded from different cell types. To substantiate the functionally defined cell types encountered in FEF, we measured the width of spikes of visual, movement, and visuomovement types of FEF neurons in macaque monkeys. We show that visuomovement neurons had the thinnest spikes, consistent with a role in local processing. Movement neurons had the widest spikes, consistent with their role in sending eye movement commands to subcortical structures such as the superior colliculus. Visual neurons had wider spikes than visuomovement neurons, consistent with their role in receiving projections from occipital and parietal cortex. These results show how structure and function of FEF can be linked to guide inferences about neuronal architecture.